The effect of the therapeutic recreation program for children with autistic spectrum disorder on their social skills - Arzu Koçak Uyaroğlu; Ezgi Ertüzün; Fatma Taş Arslan (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Background: This study was carried out to reveal the effect of the recreational therapy program on the social skills of children with autistic spectrum disorder (ASD). Material and method: The study was conducted in a one group pre experimental design with a pre-test and a post-test. The data were collected through the Family Information Form and the Autism Social Skills Profile (ASSP) Scale. To evaluate the data, t-test was performed in dependent groups. Results: It was found that the difference between the pre-test and post-test mean scores for the Social Reciprocity and Social Participation/Avoidance sub-dimensions of the scale was statistically significant; while the difference between the pre-test and post-test mean scores for the Harmful Social Behaviors sub-dimension was not statistically significant. Conclusion: It has been observed that the recreational therapy program for children with ASD affected the social skills of children positively.